Influence of undersea acoustic parameters on path loss for RF-based underwater sensor networks. (8th May 2020) - Saini, Preeti; Singh, Rishi Pal; Sinha, Adwitiya
Path loss models necessitate effective deployment of underwater sensor networks by predicting amount of loss in signal strength of the propagating wave. There are several existing path loss models that have been developed for terrestrial purpose. However, due to significant challenges unique to underwater network, these existing terrestrial models cannot be directly applied to aquatic applications. Therefore, path loss model is required to be distinctly designed for underwater applications. Three modes of underwater communication include acoustics, optics and radio waves. We have proposed a novel path loss model based on variable conductivity. Our research highlights different ways in which depth and temperature of seawater impact on signal propagating undersea. Experimental results reveal that attenuation loss confronted by deep sea is comparatively lesser than that in case of shallow water. Furthermore, communication model for deep water is also developed that combines acoustic and radio waves for communication in acoustic sensor network.